Role of Virtual Classrooms in Achieving Learning Satisfaction During COVID-19 for Students of Taiba University - Al-Ansary, Rofaydah Adnan (Journal of Educational and Psychological Sciences, 2023)
The study aimed at shedding light on the status of the use of virtual classrooms in achieving learners’ satisfaction via the digital learning systems during the COVID-19. The study adopted a survey descriptive approach. A questionnaire was designed as the study tools to apply its practical part. The sample of study composed of 95 students who were randomly selected. Many statistical styles were utilized such as frequencies, means, and standard deviation Saddam and others. Results show that the rate of the study participants attitudes towards virtual classrooms and the possible opportunities were high, whereas their perceptions towards obstacles were medium. This affirms the possibilities of learning through virtual classrooms which could possibly replace the traditional learning. The study concluded what has reached with findings and suggestions about activating virtual classrooms and ensuring improvement of educational practices, which could improve the quality and increase efficiency by best employing the virtual classroom.